15. SURVEY THE CORRELATION BETWEEN SPLENOMEGALY (ULTRASONOGRAPHICALLY DIAGNOSE) AND THE DEGREE OF ESOPHAGEAL VARICES IN CIRRHOTIC PATIENTS (Vietnam Journal of Community Medicine, 2024)
Background: Currently, many non-invasive methods have been studied for screening esophageal varices (EV) complications in patients with cirrhosis. However, the correlation between splenomegaly (on ultrasound) and the severity of EV has not been thoroughly studied in Vietnam.Objective: To investigate the correlation between splenomegaly (on ultrasound) and the severity of EV in patients with cirrhosis.Subjects and Methods: A cross-sectional descriptive study was conducted on 225 cirrhotic patients at Thong Nhat Hospital. Patients underwent biochemical tests, upper gastrointestinal endoscopy, and abdominal ultrasound. The study sought to find the correlation between the presence of splenomegaly (on ultrasound) and the presence of large EV (grade 2, grade 3).Results: The rate of EV in the study population was 82.7%, of which large EV (grade 2, grade 3) accounted for 60%. The prevalence of splenomegaly (on ultrasound) in cirrhotic patients was 31.1%. In the group with large EV (grade 2, grade 3), the prevalence of splenomegaly (on ultrasound) was 78.57%, whereas, in the group with small EV (grade 0, grade 1), the prevalence of splenomegaly (on ultrasound) was 21.43%. This difference was statistically significant (χ2 = 14.6, p = 0.005 < 0.05).Conclusion: Splenomegaly (on ultrasound) is a valuable non-invasive method for predicting the presence of large EV in patients with cirrhosis.
Keywords: Cirrhosis; large esophageal varices; Splenomegaly